2013
DOI: 10.1002/psp.1809
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Geographic Variation in US Mortality Rates Using a Spatial Durbin Approach

Abstract: Previous studies focused on identifying the determinants of mortality in US counties have examined the relationships between mortality and explanatory covariates within a county only, and have ignored the well-documented spatial dependence of mortality. We challenge earlier literature by arguing that the mortality rate of a certain county may also be associated with the features of its neighboring counties beyond its own features. Drawing from both the spillover (i.e., same direction effect) and social relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 78 publications
3
73
0
1
Order By: Relevance
“…The importance of SES has been discussed (2,26,27), and our results confirm this relationship. Income ratio is also important and our finding echoes the literature, suggesting income inequality follows the social relativity theory as neighbors with high income inequality reduce the sense of relative deprivation, which in turn improves population health (28). Moreover, prevalence of mental distress increases with the percentage of female population within (and beyond) a county.…”
Section: Discussionsupporting
confidence: 83%
“…The importance of SES has been discussed (2,26,27), and our results confirm this relationship. Income ratio is also important and our finding echoes the literature, suggesting income inequality follows the social relativity theory as neighbors with high income inequality reduce the sense of relative deprivation, which in turn improves population health (28). Moreover, prevalence of mental distress increases with the percentage of female population within (and beyond) a county.…”
Section: Discussionsupporting
confidence: 83%
“…Wilkinson, 2006; Zheng, 2012). However, as noted, there are many reasons why county is a desirable unit of analysis and several cross-sectional studies using county-level data reported a significant inequality-mortality relationship, even after accounting for the bias introduced by spatial structure (McLaughlin & Stokes, 2002; Sparks & Sparks, 2010; T.-C. Yang & Jensen, 2014; Tse-Chuan Yang, Noah, & Shoff, 2015). Putting our finding (i.e., non-significant association) into perspective and assuming that use of county as the analytic unit is appropriate, we find that controlling for the temporal trend eliminates the relationship of inequality with mortality or that the variation in inequality in the past few decades is too little to show a significant relationship with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…9 We did not adjust for characteristics of neighboring counties; we also did not account for the heterogeneity in life expectancy within counties.…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…1,39 County attributes such as rurality and social capital have previously been linked with longevity but were not included in this study. 33,34 …”
Section: Study Data and Methodsmentioning
confidence: 99%